Pengembangan Instrumen Penilaian Hasil Belajar Menggunakan Computer Based Test di SMA Negeri 10 Sidrap - Muhammad Wahyu Suryandi Adam; Hasni Hasni (Journal on Education, 2023)
This research is a research development that aims to develop products assessment instruments for learning outcomes using a valid, practical, and effective computer based test to help teachers accelerate the distribution of questions and find out the value of student learning outcomes quickly. The research method used is the Research and Development (R&D) development model with a ten-stage Dick & Carey development model, namely: analysis of needs and goals, learning analysis, analysis of learners (students) and context, formulating performance goals for work, developing instruments for test kits, developing learning strategies, developing and selecting learning materials, designing and conducting formative evaluations, make revisions, and conduct summative evaluations. Data collection techniques using questionnaires, interviews and tests which are then analyzed descriptively qualitatively and deskriptif descriptive statistics. The results showed that the development of assessment instruments for learning outcomes using the computer based test can facilitate teachers in recapitulating the value of learning outcomes for students quickly. The development of learning outcome assessment instruments using the computer based test is considered valid, practical and effective, it is obtained from the results of expert validation, teacher and student responses,and the success of learning outcomes. It isexpectedthat teachersuseproducts learning achievement assessment instruments using the computer based test in daily tests, ul mid-semester exams, and periodic end exams periodically.